The Effect of Anthocyanins from Purple Sweet Potato Extract In-vitro on IL-6 mRNA Expression in PBMC Cell Cultures Infected With Hepatitis B Virus - Made Agus Hendrayana; I Gusti Kamasan Nyoman Arijana (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: The immune system is a crucial component of the defense against viral infections.  Some cytokines directly regulate the immune response by suppressing viral replication. Interleukin-6 (IL-6) is a pleiotropic cytokine that plays a crucial role in regulating the biological responses of several target cells to viral infections. Natural compounds, such as anthocyanins, possess antiviral properties that may be beneficial in treating various viral infections. The aims of this study are to analyze the effects of anthocyanins on IL-6 expression in PBMC cultures infected with the Hepatitis B virus. Methods: This study was an in-vitro experimental study. This study used a control group and a treatment group, with 18 PBMC cell culture wells. The treatment involved adding 50 µL of purple sweet potato water extract, with an anthocyanin content of 0.01575 µg/µL, to RPMI1640 culture medium in PBMC culture wells for 24 hours. The effect on the IL-6 cytokine response was assessed by quantifying IL-6 mRNA expression in RNA isolated from PMBC cell culture samples using the quantitative real-time PCR method and interpolating from a standard curve of serial dilutions, based on cycle threshold. Data analysis was performed using statistical analysis. Results: Statistical analysis of the effects of purple sweet potato extract exposure on the treatment and control groups was carried out using a paired t-test, showing that there was an effect of exposure to purple sweet potato extract on IL-6 mRNA expression in the treatment group with a p value of 0.001 (p<0.05), while no significant effect of exposure to purple sweet potato extract was found in the control group with a p value of 0.420 (p>0.05). The results of the independent t-test showed that in the treatment group, the mean difference in IL-6 mRNA expression was -75.87±45.77 fg/µL, whereas in the control group, it was -49.26±173.70 fg/µL. In the treatment and control groups, the mean difference in IL-6 mRNA expression was -26.61 fg/µL, with a p value of 0.66 (p>0.05). Conclusion: This study showed that anthocyanins in purple sweet potato water extract did not significantly increase IL-6 mRNA expression in HBV-infected PBMC cultures compared to controls.